Bimodal expression of potential drug target CLL‐1 (CLEC12A) on CD34+ blasts of AML patients. (26th June 2021) - Ngai, Lok Lam; Ma, Connie Y.; Maguire, Orla; Do, An D.; Robert, Alberto; Logan, Aaron C.; Griffiths, Elizabeth A.; Nemeth, Michael J.; Green, Cherie; Pourmohamad, Tony; van Kuijk, Bo J.; Snel, Alexander N.; et al.
Abstract: Objectives: This study aims to retrospectively assess C‐lectin‐like molecule 1 (CLL‐1) bimodal expression on CD34+ blasts in acute myeloid leukemia (AML) patients (total N = 306) and explore potential CLL‐1 bimodal associations with leukemia and patient‐specific characteristics. Methods: Flow cytometry assays were performed to assess the deeper immunophenotyping of CLL‐1 bimodality. Cytogenetic analysis was performed to characterize the gene mutation on CLL‐1‐negative subpopulation of CLL‐1 bimodal AML samples. Results: The frequency of a bimodal pattern of CLL‐1 expression of CD34 + blasts ranged from 8% to 65% in the different cohorts. Bimodal CLL‐1 expression was most prevalent in patients with MDS‐related AML ( P = .011), ELN adverse risk ( P = .002), NPM1 wild type (WT, P = .049), FLT3 WT ( P = .035), and relatively low percentages of leukemia‐associated immunophenotypes ( P = .006). Additional immunophenotyping analysis revealed the CLL‐1 − subpopulation may consist of pre‐B cells, immature myeloblasts, and hematopoietic stem cells. Furthermore, (pre)‐leukemic mutations were detected in both CLL‐1 + and CLL‐1 − subfractions of bimodal samples (N = 3). Conclusions: C‐lectin‐like molecule 1 bimodality occurs in about 25% of AML patients and the CLL‐1 − cell population still contains malignant cells, hence it may potentially limit the effectiveness of CLL‐1‐targeted therapies and warrant further investigation.